Electrical capacitance as a predictor of root dry weight in shrub willow (Salix; Salicaceae) parents and progeny1. (19th August 2016) - Carlson, Craig H.; Smart, Lawrence B.
Abstract : Premise of the study: Root biomass is an important trait often disregarded in woody perennial selection due to the challenge and expense of accurately and efficiently measuring large populations. In this study, we aim to develop a simple method that can predict root dry weight within a diverse shrub willow ( Salix ) breeding population representing species hybrids and their parents using root electrical capacitance (REC). Methods: The REC method was tested on plants started from cuttings and grown in pots with potting mix in the greenhouse for 11 wk to assess the relationship of REC with 24 biomass traits and its usefulness in allometric models for root and stem dry biomass. Results: Strong linear and positive correlations were found between REC and root dry biomass ( r = 0.88). The total proportion of variance of root and stem dry biomass explained by predictors in multiple regression was 85% and 69%, respectively. The relative importance of predictor variables in allometric models was dominated by the contribution of REC. Discussion: This work provides an efficient and nondestructive technique to indirectly quantify root biomass of genetically diverse shrub willow progeny, which has great promise for selection of genotypes with varying root biomass and for the accurate estimation of belowground carbon sequestration.